Identification of financial and macroeconomic shocks in a VAR model of the Polish economy. A stability analysis - Ulrichs, Magdalena (Economics and Business Review, 2018)
Dynamic macroeconomic models (both VAR and DSGE) currently playa very significant role in macroeconomic modelling. But these types of models rarelytake into account the impact of financial markets on the behaviour of economies, theyare rather more focused on the monetary transmission mechanism. The financial crisisof 2007-2008 highlighted the impact of the financial market on the macroeconomy.In this context macroprudential policy and financial stability analysis has gaineda stronger meaning. The main aim of the paper is to estimate a model that simultaneouslyexplains the dynamics of macroeconomic and financial variables and to assesswhether the identified relationships are stable over time. Therefore, based on the estimatedempirical structural vector autoregression model explaining the interactionsbetween the real economy, the financial system and monetary policy in Poland, financialand macroeconomic shocks were identified. It was shown that the impulse reactionfunctions changed after the financial crisis. On the basis of Markov‑Switching vectorautoregression model probabilities of transitions between states of the economy andthe regime-dependent impulse reaction functions were estimated.